2018
DOI: 10.1016/j.jphys.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Trial Protocol: Cognitive functional therapy compared with combined manual therapy and motor control exercise for people with non-specific chronic low back pain: protocol for a randomised, controlled trial

Abstract: This study will investigate whether the results of the first cognitive functional therapy randomised clinical trial are reproducible. The present study will have a sample size capable of detecting clinically relevant effects of the treatment with a low risk of bias. In pragmatic terms, this clinical trial is designed to reproduce the intervention as it would be performed in clinical practice by a trained physiotherapist who works with cognitive functional therapy, which increases the relevance of this study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Clinical studies have reported that patients with LBP often exhibit obsessive‐compulsive disorder, panic disorder, and anxiety 22,23 . Anxiety disorders aggravate the occurrence and development of LBP, and the relationship between LBP and anxiety has recently attracted growing attention 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have reported that patients with LBP often exhibit obsessive‐compulsive disorder, panic disorder, and anxiety 22,23 . Anxiety disorders aggravate the occurrence and development of LBP, and the relationship between LBP and anxiety has recently attracted growing attention 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of psychological factors as anxiety and insecurity in people with low back symptoms is associated with the risk of developing disability (Hartvigsen et al, 2018;Lardon et al, 2018). Anxiety, is also, associated with pain, growth of symptomatology and pain behaviors (Andersen et al, 2018;Belache et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“… 36 Lately, there has been a shift towards incorporating pain education and CB treatment approaches by PT’s for the treatment of back pain. 37 , 38 In this systematic review, the inclusion criteria involve every field of the cognitive-behavioral and biopsychosocial parameters.…”
Section: Discussionmentioning
confidence: 99%